A histone deacetylase inhibitor enhances rice immunity by derepressing the expression of defense-related genes - Xu, Yan; Miao, Yuanxin; Cai, Botao; Yi, Qingping; Tian, Xuejun; Wang, Qihai; Ma, Dan; Luo, Qiong; Tan, Feng; Hu, Yongfeng (Frontiers in Plant Science, 2022)
Histone deacetylase (HDAC) inhibitors (HDACis) have been widely used in plants to investigate the role of histone acetylation, particularly the function of HDACs, in the regulation of development and stress response. However, how histone acetylation is involved in rice (Oryza sativa L.) disease resistance has hardly been studied. In this paper, four HDACis including Sodium butyrate (NaBT), Suberoylanilide Hydroxamic Acid (SAHA), LBH-589 and Trichostatin A (TSA) were used to treat rice seedlings at different concentrations before inoculation of Magnaporthe oryzae. We found that only 10mM NaBT treatment can significantly enhanced rice blast resistance. However, treatment of the four HDACis all increased global histone acetylation but at different sites, suggesting that the inhibition selectivity of these HDACis is different. Notably, the global H3K9ac level was dramatically elevated after both NaBT and LBH589 treatment although LBH589 could not enhance rice blast resistance. This indicates that the HDACs they inhibit target different genes. In accordance with the phenotype, transcriptomic analysis showed that many defense-related genes were up-regulated by NaBT treatment. Up-regulation of the four genes bsr-d1, PR10B, OsNAC4, OsKS4 were confirmed by RT-qPCR. ChIP-qPCR results revealed that H3K9ac levels on these genes were increased after NaBT treatment, suggesting that these defense-related genes were repressed by HDACs. In addition, by promoter motif analysis of the genes that induced by both NaBT treatment and rice blast infection, we found that the motifs bound by ERF and AHL transcription factors (TFs) were the most abundant, which demonstrates that ERF and AHL proteins may act as the candidate TFs that recruit HDACs to defense-related genes to repress their expression when plants are not infected by rice blast.